(untitled) (Journal of Mathematical Study, 2023)
Research on the Julia sets of meromorphic functions has been one of the hot topics in complex dynamics. In this paper, we shall investigate the radial distribution of the Julia sets of entire functions which are extremal for some famous inequalities. Our estimates for these particular functions are more accurate than others.